The Future of Pig Liver Xenotransplantation - Ahmad Karadagi; Ahmad Karadagi; Gabriel C. Oniscu; Gabriel C. Oniscu (Transplant International)
Recent technological advances in genetic engineering have led to a renewed interest in xenotransplantation. Milestones achievements in heart, kidney and more recently liver xenotransplantation raise the hope of an alternative source of organs and pave the way for first in human clinical trials. With these rapid developments, it is important to consider what may be the place of liver xenotransplantation in the treatment armamentarium and what are the challenges to achieve clinical liver xenotransplantation.